2001
DOI: 10.1130/0091-7613(2001)029<0351:rascom>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and synchronous collapse of marine and terrestrial ecosystems during the end-Permian biotic crisis

Abstract: A newly studied Permian-Triassic (P-Tr) boundary section in Jameson Land, East Greenland, contains an abundant and well-preserved marine fauna as well as terrestrial palynomorphs. For the first time it is possible to compare the biotic crises of the marine and terrestrial realms using the same samples from the same section. The sediments record a negative excursion in δ 13 C carb values of 8‰-9‰, and in δ 13 C org values of 10‰-11‰. The presence of the conodont Hindeodus parvus, combined with the δ 13 C carb r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
203
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(225 citation statements)
references
References 11 publications
18
203
1
3
Order By: Relevance
“…To better understand the relationship between environmental perturbation and biotic response, accurate and precise age models that integrate geochronology, paleontology, and geochemistry must be developed (8,11,16,17). Recognition of astronomically forced sedimentary cycles (Milankovitch cycles) in late Permian and Triassic sedimentary rocks tuned with available geochronology have been used to refine existing age models of the biotic crisis (18)(19)(20).…”
Section: ± 028 Ma (54)mentioning
confidence: 99%
“…To better understand the relationship between environmental perturbation and biotic response, accurate and precise age models that integrate geochronology, paleontology, and geochemistry must be developed (8,11,16,17). Recognition of astronomically forced sedimentary cycles (Milankovitch cycles) in late Permian and Triassic sedimentary rocks tuned with available geochronology have been used to refine existing age models of the biotic crisis (18)(19)(20).…”
Section: ± 028 Ma (54)mentioning
confidence: 99%
“…1-3) suggests that per-plate extinction risk varied considerably among genera. Each of these events also is associated with geological and geochemical evidence for rapid, global environmental disruption coincident with geologically rapid extinction (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Previous studies have identified ecological and physiological extinction selectivity patterns that may account for differences in per-plate extinction risk among genera during these intervals.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that in the face of elevated pCO 2 conditions, such as those experienced, for example, during the PermoTriassic boundary [112][113][114][115], the evolution (or development) of moderate metabolic depression may have enabled some marine organisms to persist locally and globally. This may have come, however, at the cost of some life-history traits, such as reduced body size: see [116] for a review on the Lilliput Effect.…”
Section: (A) Discriminating Between Acclimatization and Adaptationmentioning
confidence: 99%